Integration of STEM Education to Humanities: Examining Interdisciplinary Links in Basic Chemistry Course According to Student Views - DOĞRU, Said (Research on Education and Psychology, 2023)
Science standards for the next generation, as well as other educational reforms, encourage the creation of solid ties between STEM disciplines. Education societies regard integrated STEM as the best practice in various fields. Besides, the integration of disciplines other than STEM has yet to be adequately studied, and the integration of artistic disciplines is limited. Humanist STEM combines the STEM studies in terms of culture, human relationships, level of well-being, and values. This study investigates whether incorporating humanities in an electronic chemistry lecture affects student communication between course themes and interdisciplinary viewpoints. Students were explicitly asked to link STEM subjects between the scientific and the non-scientific, between the scientific and the physical reality from a broader scientific view. This study was conducted with 85 first-year student-teacher candidates studying at the Faculty of Education, Department of Mathematics and Science Education of a Western Black Sea region university in the 2019-2020 academic year. In the study, homework was designed to make evaluations throughout the course. In addition, cross-sectional study analysis was used in the study. A 5-point Likert-type scale was used. All data were analyzed with StatDisk 13 using the required 2 (chi-square) tests. In the data obtained from the research, most students agree that education creates a strong relationship and understanding between science and other undergraduate courses and STEM fields, humanities, and the environment in which they live. This has been observed in traditional (practical) and interdisciplinary (post-implementation) approaches. The findings from this study contribute to the idea of positively altering interdisciplinary perspectives as part of an introductory chemistry course. Today, it is seen that multidisciplinary science is widespread in the fields, and our academic courses need to be shaped according to the specific discipline approaches desired.
Keywords: Eğitim Psikolojisi; Basic chemistry course; Multidisciplinary approach; Humanistic and integrated STEM; Science education; Educational Psychology; 4. Education